2014
DOI: 10.1080/13562517.2014.957269
|View full text |Cite
|
Sign up to set email alerts
|

‘The thing that kill us’: student perspectives on language support in a South African university

Abstract: South African higher education institutions, in line with international practice and as a result of the 'social turn', are progressing towards mainstream academic literacy support for students. This shift has a political dimension in South Africa where, historically, disadvantage has had racial dimensions, in its departure from 'deficit' models of academic development and support. On the other hand, there are practical factors to be considered in the kinds of support we offer students. This article describes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Supported by earlier research, in this study, cultural and social capital relate to the importance of communication, friendship and working relationships in international students' development of belonging and institutional habitus (Leese, 2010;Pitman and Vidovitch, 2013;Gale and Parker, 2014;Hurst, 2015). Academic and linguistic capital are concerned with such students' knowledge acquisition and their development of academic and linguistic confidence and success (Leese, 2010;Pitman and Vidovitch, 2013;Gale and Parker, 2014;Hurst, 2015).…”
Section: Conceptualising First Year International Student Transition:mentioning
confidence: 67%
“…Supported by earlier research, in this study, cultural and social capital relate to the importance of communication, friendship and working relationships in international students' development of belonging and institutional habitus (Leese, 2010;Pitman and Vidovitch, 2013;Gale and Parker, 2014;Hurst, 2015). Academic and linguistic capital are concerned with such students' knowledge acquisition and their development of academic and linguistic confidence and success (Leese, 2010;Pitman and Vidovitch, 2013;Gale and Parker, 2014;Hurst, 2015).…”
Section: Conceptualising First Year International Student Transition:mentioning
confidence: 67%
“…It has been revealed that the motivation level in language learning of females is higher than that of males. According to Hurst (2015), in order to improve communicative skills in English, it is necessary for learners to use this language in their daily life. Using the target language on campus life, in the language classes, they are developing their language skills day by day.…”
Section: Resultsmentioning
confidence: 99%
“…The South African higher education sector has implemented policies aimed at widening access to historically disadvantaged students, and while these policies have enjoyed some measure of success, the wider access has yet to translate into equitable success among these students (Frempong, Reddy, & Kanjee, 2011). English proficiency has been identified as one of the primary barriers to student success in tertiary education and is seen as reflective of students’ access to quality education in primary and high school (Hurst, 2015; Kamwangamalu, 2000). In addition to the fact that most South African higher education students do not study in their mother tongue, economic inequalities continue to shape student outcomes through university fee structures that are beyond the means of most families.…”
mentioning
confidence: 99%